The Impact of Traditional Dance on Physical Fitness and Coordination in Spain - Ana María García, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Besides being a cultural phenomenon, traditional Spanish dancing effectively improves coordination and physical fitness. The research investigates the complex effects of ancient Spanish dance styles, including jota, flamenco, and sevillanas, on the physical health of its practitioners in Spain. By analyzing the expressive gestures, rhythmic footwork, and cultural importance of these dances, we find the many ways that these dances improve cardiovascular health, muscular strength, flexibility, balance, and coordination. We also explore traditional Spanish dance's social and emotional dimensions, emphasizing how it may support mental health and participants' feelings of cultural identification and belonging. Moreover, the social dimension of traditional Spanish dance cultivates a feeling of unity and inclusion among participants, establishing a nurturing atmosphere where people may strive towards their health objectives while relishing the delight of dancing. Dancers create connections via group courses, rehearsals, and performances that cut over cultural divides and bring people from all walks of life together through a common love of movement and expression. To sum up, traditional Spanish dance integrates creative expression, cultural legacy, and physical well-being in a comprehensive physical training and coordination approach. From its beginnings in the many areas of Spain to its widespread appeal on the international scene, traditional dance is a living example of the timeless power of music and movement. This study illuminates the transformational potential of traditional Spanish dancing as an art form and a way to improve physical fitness and coordination by referencing historical perspectives, cultural context, and scientific research.